Urticarial vasculitis: Etiologies and clinical course - Kanokvalai Kulthanan (2018)
Out of 64 patients diagnosed with urticarial vasculitis (UV), 49 (76.6%) presented with their first attack of UV. The others experienced recurrent attacks with a mean number of 3.3 past recurrences. Fifteen patients had angioedema (23.4%) and 16 (25%) suffered systemic involvement. The most common abnormal laboratory finding was an increased erythrocyte sedimentation rate. Six of 62 patients (9.7%) had decreased C3 levels. A cause could be identified in 19 patients (29.7%). The most common identified cause was infection; other causes included drugs, malignancy and systemic lupus erythematosus (SLE). The prevalence of immunoreactant deposits in the skin lesions measured by DIF was 54.7% (35 of 64 patients). The median disease duration of each episode was 85 days. The probability that patients were free of symptoms within one year was 70%. Patients with an idiopathic cause had a statistically significant longer course duration of each episode than the group with upper respiratory tract infection. Compared to reports from Western countries, our patients seemed to have less severe symp-toms and a lower percentage of hypocomplementemic UV and SLE.